COD, TSS, NUTRIENTS AND COLIFORMS REMOVALS IN UASB REACTORS IN TWO STAGES TREATING SWINE WASTEWATER - Del'Arco Ramires, Roseane [UNESP]; De Oliveira, Roberto Alves [UNESP] (Soc Brasil Engenharia Agricola, 2014)
The performance of two upflow anaerobic sludge blanket (UASB) reactors was evaluated in pilot scale (908 and 188 L), installed in series (R1 and R2), fed with swine wastewater with TSS around 5 and 13 g L-1. The UASB reactors were submitted to HDT of 36 and 18 h with VOL of 5.5 to 34.4 g COD (L d)(-1) in the R1 and HDT of 7.5 e 3.7 h with VOL from 5.1 to 45.2 g COD (L d)(-1) in the R2. The average removal efficiencies of COD ranged from 55 to 85% in the R1 and from 43 to 57% in the R2, resulting in values from 82 to 93% in the UASB reactors in two stage. Methane concentrations in the biogas were 69 to 74% with specific production from 0.05 to 0.27 L CH4 (g removedCOD)(-1) in the R1 and of 0.10 to 0.12 L CH4 (g removedCOD)(-1) in the R2. The average removal efficiencies were 61 to 75% for P-total, 39 to 69% for KN, 82 to 93% for N-org and 20 to 94% for Fe, Zn, Cu and Mn. The N-am concentration were not reduced indicating the need to post-treatment for effluent disposal into water bodies. There were reductions of total coliforms from 99.8123 to 99.9989% and of thermotolerant coliforms from 99.9725 to 99.9999%. The conditions imposed to the UASB reactors in two stage provided high conversions of removedCOD into methane (up to 77%) and reductions of organic an inorganic pollution loads from swine wastewater.
Keywords: volumetric organic load; methane; N and P removal; metal removal; suspended solids